Assessment of the neuroprotective potential of d-cycloserine and l-serine in aluminum chloride-induced experimental models of Alzheimer’s disease: In vivo and in vitro studies - Tozlu, Özlem Özdemir; Türkez, Hasan; Okkay, Ufuk; Ceylan, Onur; Bayram, Cemil; Hacımüftüoğlu, Ahmet; Mardinoğlu, Adil (Frontiers in Nutrition, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disease characterized by the accumulation of amyloid-β (Aβ) plaques and neurofibrillary tangles in the brain accompanied by synaptic dysfunction and neurodegeneration. No effective treatment has been found to slow the progression of the disease. Therapeutic studies using experimental animal models have therefore become very important. Therefore, this study aimed to investigate the possible neuroprotective effect of D-cycloserine and L-serine against aluminum chloride (AlCl3)-induced AD in rats. Administration of AlCl3 for 28 days caused oxidative stress and neurodegeneration compared to the control group. In addition, we found that aluminum decreases α-secretase activity while increasing β-secretase and γ-secretase activities by molecular genetic analysis. D-cycloserine and L-serine application resulted in an improvement in neurodegeneration and oxidative damage caused by aluminum toxicity. It is believed that the results of this study will contribute to the synthesis of new compounds with improved potential against AlCl3-induced neurodegeneration, cognitive impairment, and drug development research.